HYPOGLYCEMIC EFFECT OF SITAGLIPTIN AND AMINOGUANIDINE COMBINATION IN EXPERIMENTAL DIABETES MELLITUS - D. V. Kurkin; D. A. Bakulin; E. I. Morkovin; Yu. V. Gorbunova; A. V. Strygin; T. M. Andriashvili; A. A. Sokolova; N. S. Bolokhov; V. E. Pustynnikov; E. A. Fomichev (Фармация и фармакология (Пятигорск))
The aim of the work was to determine the antidiabetic effect of a sitagliptin and aminoguanidine combination in rats with experimental diabetes mellitus.Materials and methods. The study was carried out on male Wistar rats and C57BL/KsJ-db/db mice. According to the models used, it was divided into 4 series, in which alloxan, steroid-induced (dexamethasone) and streptozotocin-nicotinamide-induced diabetes mellitus (DM) were formed, respectively, in rats, and in the 4 series, obese C57BL/KsJ-db/db mice were used. In the 1 and 2 series, the treatment was started prophylactically – 3 h after the alloxan administration and simultaneously with the dexamethasone administration, in the 3rd and 4th series, the treatment was carried out after the pathology had developed – 7 days after the streptozotocin with nicotinamide administration, and in the obese mice – immediately after their distribution according to the groups. The treatment was carried out with sitagliptin (10 mg/kg), aminoguanidine (25 mg/kg), or a combination thereof. The treatment was continued till the end of the experiment, which was completed with an oral glucose tolerance test (OGTT) after 4 h of fasting. The obtained data were subjected to statistical processing.Results. In the course of the experiments, it was found out that the prophylactic administration of a sitagliptin and aminoguanidine combination, unlike each of the components, prevented the development of alloxan DM. More effectively than the administration of sitagliptin alone, it reduced the severity of steroid-induced DM, which was expressed in a significantly lower level of fasting glycemia (after 4 h of fasting) and postprandial glycemia (during OGTT). Under the conditions of streptozotocin-nicotinamide-induced DM, the studied combination slowed down the progression of the pathology, and in the obese mice, the course therapeutic administration of sitagliptin and its combination reduced the severity of carbohydrate metabolism disorders (fasting glycemia) and increased the rate of glucose utilization.Conclusion. As an iNOS blocker, aminoguanidine enhances the antidiabetic effect of sitagliptin, preventing the development of alloxan diabetes and reducing the severity of steroid-induced DM when administered prophylactically. When administered therapeutically, it reduces the severity of streptozotocin-nicotinamide-induced DM in rats and type 2 DM in mice with a predisposition to obesity.